Strength Development of High-Strength Ductile Concrete Incorporating Metakaolin and PVA Fibers - Muhammad Fadhil Nuruddin; Sadaqat Ullah Khan; Nasir Shafiq; Tehmina Ayub (The Scientific World Journal)
The mechanical properties of high-strength ductile concrete (HSDC) have been investigated using Metakaolin (MK) as the cement replacing material and PVA fibers. Total twenty-seven (27) mixes of concrete have been examined with varying content of MK and PVA fibers. It has been found that the coarser type PVA fibers provide strengths competitive to control or higher than control. Concrete with coarser type PVA fibers has also refined microstructure, but the microstructure has been undergone with the increase in aspect ratio of fibers. The microstructure of concrete with MK has also more refined and packing of material is much better with MK. PVA fibers not only give higher stiffness but also showed the deflection hardening response. Toughness Index of HSDC reflects the improvement in flexural toughness over the plain concrete and the maximum toughness indices have been observed with 10% MK and 2% volume fraction of PVA fibers.